Petrochemistry of contrasting late Precambrian volcanic and plutonic associations, Caledonian Highlands, Southern New Brunswick - Barr, Sandra M.; White, Chris E. (Atlantic Geoscience, 1988)
The eastern Caledonian Highlands of southern New Brunswick consist mainly of greenschist-facies or subgreenschist-facics volcanic, sedimentary, and plutonic rocks generally considered to be typical of Late Precambrian sequences in the Avalon Terrane of the northern Appalachian Orogen. As aresult of regional mapping combined with petrological studies and radiometric dating, these rocks in the eastern Caledonian Highlands have been divided into two contrasting groups. The older group, apparently ranging in age from about 600 to 630 Ma, consists of metatuffaceous rocks ranging from mafic to felsic in composition, fine-grained volcanogenic metasedimentary rocks (slate and phyllite), arkosic metasedimentary rocks, and dioritic to granitic plutons. The volcanic rocks appear to be calc-alkalic, and both the volcanic and plutonic rocks were formed in a subduction-related tectonic setting. In contrast, the other group of rocks appears to be about 550 Ma in age and consists of arkosic sedimentary rocks, subaerial rhyolite and basalt flows, laminated siltstone, felsic lapilli tuff, volcaniclastic conglomerate, and plutons of mainly gabbrotc and syenogranitic composition. These units typically are much less deformed and metamorphosed than die older group of units. The volcanic and plutonic rocks appear to be cogenetic bimodal suites, with petrochemical characteristics suggesting that they formed in a rifting environment -within an older volcanic arc. RÉSUMÉ Les Monts Calédoniens orientaux (Nouveau-Brunswick méridional) sont constitués surtout de roches volcaniques, sédimeniaires et plutoniques métamorphisées dans le fades des schistes verts (ou presque), généralement considerées comme typiques des séries lardiprécambriennes de la Lanière d’Avalon de l’Orogène appalachien septentrional. À la suite d’un lever régional combing à des études pétrologiques et des datations radiométriques, on a divisé ces roches des Monts Caledoniens orientaux en deux groupes distincts. Le plus ancien groupe, qui s’échelorme vraisemblablement d’environ 600 à 630 Ma, comprend des roches a métatufs de composition mafique à felsique, des roches métasédimentaires volcanogéniques à grain fin (ardoise et phyllade), des roches métasédimentaires arkosiques et des plutons dioritiques à granitiques. Les volcanites semblent être calco alcalines. Les volcanites comme les plutonites furent engendrées dans un contexte tectonique lié à une subduction. Par contre, l’autre groupe de roches semble dater d’environ 550 Ma et comprend des roches sédimentaires arkosiques, des épanchements subaériens de basalte et de rhyolite, des siltstones laminés des tufs a lapilli felsiques, des poudingues volcaniclastiques, ainsi que des plutons à composition principalement gabbroique et syénogranitique. Ces unités sont typiquement beaucoup moins déformées et métamorphisées que l’est le groupe d’unités plus ancien. Les volcanites et les plutonites semblent appartenir à des lignées cogenétiques bimodales; leurs caracteres pétrochimiques suggérent une génèse au sein d’un arc volcanique en contexte de rift. [Traduit par le journal]